Impacts of Extrinsic and Intrinsic reward on Employee’s performance: A study of banking sector in Pakistan - Moeen Ul Haq; Muhammad Waqas Qazi; Muhammad Kamran; Maira Yosaf (Journal of Management Practices, Humanities and Social Sciences, 2023)
The aim of this study was to find the impact of reward on employee performance. Reward is divided in to two parts i.e. intrinsic incentives and extrinsic incentive. The intrinsic reward refers to the motivating forces which attributes to the work itself while the extrinsic rewards are the ones which are offered to the employees for doing or completions of specific task, duties or objectives. This study was conducted In Habib Bank Limited (Pvt) in Pakistan. A total of (n=200) was selected for this study and data was collected from these employee from different branches through convenient sampling technique. The results of this study revealed that alpha reliability of all variables of this study are reliable. The results also show that intrinsic incentive has positive and significant impact on employee performance and extrinsic incentive also has significant and positive impact on employee performance. Moreover, the results also revealed that multiple regressions of both intrinsic incentive and extrinsic incentive have positive and significant impact on employee performance. This study will also contribute in the area of management and Human resource management.